The Enigma of Fichte's First Principles - Wood, David W., (Fichte-Studien ;, 2021)
Presenting new critical perspectives on J.G. Fichte's Wissenschaftslehre , this volume of English articles by an international group of scholars addresses the topic of first principles in Fichte's writings. Especially discussed are the central text of his Jena period, the 1794/95 Grundlage der gesammten Wissenschaftslehre , as well as later versions like the Wissenschaftslehre nova methodo (1796-99) and the presentations of 1804 and 1805. Also included are new studies on the first principles of the particular sub-disciplines of Fichte's system, such as the doctrines of aesthetics, nature, right, ethics, and history.